북한이탈주민진료센터 정신건강의학과를 내원한 북한이탈주민에서 외상 후 스트레스장애와 사회 적응 및 삶의 질 관계 - 한나영, 이소희, 유소영, 김석주, 전진용, 원성두, 신미녀 (Singyŏng chŏngsin ŭihak, 2015)
Objectives ZZThis study was conducted to evaluate post-traumatic stress disorder (PTSD), thequality of life and social adjustment of North Korean refugees who consulted psychiatric clinics. MethodsZZA total of 66 North Korean refugees who consulted a psychiatric clinic were includedin the analysis. A psychiatrist conducted interviews with the subjects, and PTSD was diagnosedusing the clinician-administered PTSD Scale. The quality of life of the subjects was evaluated usingthe World Health Organization Quality of Life Scale. ResultsZZThirty five (53%) were diagnosed with PTSD. Quality of life was found to show associationwith understanding the language in South Korea, difficulty interacting with South Koreans,and experience or feeling of neglect. Quality of life of the PTSD grou p was lower than in the Non-PTSD group. Difficulty adapting to South Korean society was also higher in the PTSD group. Experienceor feeling of neglect was negatively correlated with the quality of life in the PTSD group. ConclusionZZThe results of this study may be helpful in providing a specific direction for psychiatricintervention strategies to improve overall quality of life and adaptation to life in South Korea. KCI Citation Count: 7